The American jury system - Jonakait, Randolph N. (Contemporary law series., 2003)
How are juries selected in the United States? What forces influence juries in making their decisions? Are some cases simply beyond the ability of juries to decide? How useful is the entire jury system?In this important and accessible book, a prominent expert on constitutional law examines these and other issues concerning the American jury system. Randolph N. Jonakait describes the historical and social pressures that have driven the development of the jury system; contrasts the American jury system to the legal process in other countries; reveals subtle changes in the popular view of juries; examines how the news media, movies, and books portray and even affect the system; and discusses the empirical data that show how juries actually operate and what influences their decisions. Jonakait endorses the jury system in both civil and criminal cases, spelling out the important social role juries play in legitimizing and affirming the American justice system.